# |
ODE |
Mathematica |
Maple |
\[
{}\left (x -1\right ) y^{\prime }+y-\frac {1}{x^{2}}+\frac {2}{x^{3}} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x y^{2}-\frac {2 y}{x}-\frac {1}{x^{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 y^{2}}{x}+\frac {y}{x}-2 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2} {\mathrm e}^{-x}+y-{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }-x y = \frac {1}{x}
\] |
✓ |
✓ |
|
\[
{}x \ln \left (y\right ) y^{\prime }-y \ln \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}2 x -y \sin \left (2 x \right ) = \left (\sin \left (x \right )^{2}-2 y\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}3 x^{3} y^{2} y^{\prime }-x^{2} y^{3} = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 y-y^{2} {\mathrm e}^{3 x} = 0
\] |
✓ |
✓ |
|
\[
{}u \left (-v +1\right )+v^{2} \left (1-u\right ) u^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y+2 x -x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (y+2 x \right ) y^{\prime }-x +2 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x \cos \left (y\right )-{\mathrm e}^{-\sin \left (y\right )}\right ) y^{\prime }+1 = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right )^{2} y^{\prime }+\sin \left (x \right )^{2}+\left (x +y\right ) \sin \left (2 x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+x y = \frac {x}{y}
\] |
✓ |
✓ |
|
\[
{}\sin \left (\theta \right ) \cos \left (\theta \right ) r^{\prime }-\sin \left (\theta \right )^{2} = r \cos \left (\theta \right )^{2}
\] |
✓ |
✓ |
|
\[
{}3 x^{2} y+x^{3} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = x^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = x y+y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 x^{2} y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\sin \left (x +y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 4 y^{2}-3 y+1
\] |
✓ |
✓ |
|
\[
{}s^{\prime } = t \ln \left (s^{2 t}\right )+8 t^{2}
\] |
✓ |
✗ |
|
\[
{}y^{\prime } = \frac {y \,{\mathrm e}^{x +y}}{x^{2}+2}
\] |
✓ |
✓ |
|
\[
{}\left (x y^{2}+3 y^{2}\right ) y^{\prime }-2 x = 0
\] |
✓ |
✓ |
|
\[
{}s^{2}+s^{\prime } = \frac {s+1}{s t}
\] |
✗ |
✗ |
|
\[
{}x y^{\prime } = \frac {1}{y^{3}}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = 3 x t^{2}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \frac {t \,{\mathrm e}^{-t -2 x}}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x}{y^{2} \sqrt {1+x}}
\] |
✓ |
✓ |
|
\[
{}x v^{\prime } = \frac {1-4 v^{2}}{3 v}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\sec \left (y\right )^{2}}{x^{2}+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 x^{2} \left (1+y^{2}\right )^{{3}/{2}}
\] |
✓ |
✓ |
|
\[
{}x^{\prime }-x^{3} = x
\] |
✓ |
✓ |
|
\[
{}x +x y^{2}+{\mathrm e}^{x^{2}} y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {y^{\prime }}{y}+y \,{\mathrm e}^{\cos \left (x \right )} \sin \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (1+y^{2}\right ) \tan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{3} \left (1-y\right )
\] |
✓ |
✓ |
|
\[
{}\frac {y^{\prime }}{2} = \sqrt {1+y}\, \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = \frac {4 x^{2}-x -2}{\left (1+x \right ) \left (1+y\right )}
\] |
✓ |
✓ |
|
\[
{}\frac {y^{\prime }}{\theta } = \frac {y \sin \left (\theta \right )}{y^{2}+1}
\] |
✓ |
✓ |
|
\[
{}x^{2}+2 y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 t \cos \left (y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 8 x^{3} {\mathrm e}^{-2 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2} \left (1+y\right )
\] |
✓ |
✓ |
|
\[
{}\sqrt {y}+\left (1+x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {{\mathrm e}^{x^{2}}}{y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {\sin \left (x \right )+1}\, \left (1+y^{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 y-2 t y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{{1}/{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{{1}/{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (x -3\right ) \left (1+y\right )^{{2}/{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}-3 y+2
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+\sin \left (x \right )-y = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime }+t x = {\mathrm e}^{x}
\] |
✗ |
✗ |
|
\[
{}\left (t^{2}+1\right ) y^{\prime } = t y-y
\] |
✓ |
✓ |
|
\[
{}3 t = {\mathrm e}^{t} y^{\prime }+y \ln \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x x^{\prime }+x t^{2} = \sin \left (t \right )
\] |
✗ |
✗ |
|
\[
{}3 r = r^{\prime }-\theta ^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y-{\mathrm e}^{3 x} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{x}+2 x +1
\] |
✓ |
✓ |
|
\[
{}r^{\prime }+r \tan \left (\theta \right ) = \sec \left (\theta \right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+2 y = \frac {1}{x^{3}}
\] |
✓ |
✓ |
|
\[
{}t +y+1-y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2} {\mathrm e}^{-4 x}-4 y
\] |
✓ |
✓ |
|
\[
{}y x^{\prime }+2 x = 5 y^{3}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+3 x^{2}+3 y = \frac {\sin \left (x \right )}{x}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime }+x y-x = 0
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime }-x^{2} y = \left (1+x \right ) \sqrt {-x^{2}+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y}{x} = x \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+4 y-{\mathrm e}^{-x} = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} x^{\prime }+3 t x = t^{4} \ln \left (t \right )+1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {3 y}{x}+2 = 3 x
\] |
✓ |
✓ |
|
\[
{}\cos \left (x \right ) y^{\prime }+y \sin \left (x \right ) = 2 x \cos \left (x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) y^{\prime }+y \cos \left (x \right ) = x \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \sqrt {1+\sin \left (x \right )^{2}} = x
\] |
✓ |
✓ |
|
\[
{}\left ({\mathrm e}^{4 y}+2 x \right ) y^{\prime }-1 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = \frac {x}{y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {3 y}{x} = x^{2}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \alpha -\beta \cos \left (\frac {\pi t}{12}\right )-k x
\] |
✓ |
✓ |
|
\[
{}u^{\prime } = \alpha \left (1-u\right )-\beta u
\] |
✓ |
✓ |
|
\[
{}x^{2} y+x^{4} \cos \left (x \right )-x^{3} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{{10}/{3}}-2 y+x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sqrt {-2 y-y^{2}}+\left (-x^{2}+2 x +3\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \,{\mathrm e}^{x y}+2 x +\left (x \,{\mathrm e}^{x y}-2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}+\left (2 x y+\cos \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x +y \cos \left (x y\right )+\left (x \cos \left (x y\right )-2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\theta r^{\prime }+3 r-\theta -1 = 0
\] |
✓ |
✓ |
|
\[
{}2 x y+3+\left (x^{2}-1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x -2 y\right ) y^{\prime }+2 x +y = 0
\] |
✓ |
✓ |
|
\[
{}\cos \left (x \right ) \cos \left (y\right )+2 x -\left (\sin \left (x \right ) \sin \left (y\right )+2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{t} \left (y-t \right )+\left (1+{\mathrm e}^{t}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {t y^{\prime }}{y}+1+\ln \left (y\right ) = 0
\] |
✓ |
✓ |
|